Application of Eco Tropical Themes and Concepts in Rehabilitation and Beach Security Training Centers in Buleleng, Bali - Kurniawan, Made Ngurah Viko; Rajendra, , I Gusti Ngurah Anom; Salain, I Ketut Muliawan (Journal of A Sustainable Global South; Vol 2 No 2 (2018): August 2018DO - 10.24843/jsgs.2018.v02.i02.p06, 2018)
The Rehabilitation and Coast Security Training Center is a place that designed to accommodate training activities from Coastal Rehabilitation and Coastal Management. The Coast Security Rehabilitation and Training Center is an organi-zation under the Regional Disaster Management Agency, in this planning the building will be designed in the Buleleng area due to several supporting factors, namely, in the province of Bali the Buleleng area has the longest coastline area others in Bali there are 172,301 Km (BPS Buleleng 2015). So that it needs a forum to train people to protect the coast and preserve the existing beaches, other factors that determine the Buleleng area, especially on Sawan Sangsit vil-lage, have similar organizations so expected the building designed will accommodate the activities of the existing or-ganization in the Buleleng area. In the process of designing the Beach Security and Rehabilitation Training Center, it starts from determining the theme by observing the condition of the surrounding area and adjusting it to local customs and culture so that the appearance of buildings can be in harmony with the appearance of the surrounding buildings and acceptable to the community. Index Terms — training center, rehabilitation, coastal security, buleleng, bali.